Criminogenic Needs as Intervening Factors in the Relation Between Insecure Attachments and Youth Sexual Violence. (April 2020) - Yoder, Jamie; Grady, Melissa D.; Brown, Adam; Dillard, Rebecca
There is a strong theoretical and research base demonstrating the link between attachment styles and adolescent sexual offending. However, this relationship may be best explained by deficit-based mediational pathways including criminogenic needs such as emotional or affect regulation and callousness. Grady, Levenson, and Bolder propose a framework that details criminogenic needs as intermediary variables in the attachment–sexual offending relationship. Using data on adolescents adjudicated of sexual and nonsexual crimes in a Western state ( N = 200), two structural equation models (SEM) tested direct and indirect relationships between ambivalent and avoidant attachment styles (in separate models), dysregulation including cognitive and behavioral transitions, emotional control, and inhibited/impulsive behaviors, callousness, delinquency, and offending type (sexual or nonsexual offending). Results revealed statistically significant direct pathways between variables of interest and a multimediational effect of dysregulation and callousness in the relationship between insecure attachments and sexual offending. Treatment, policy, and research implications are discussed.